Respuesta :
Answer:
1.27 m/s
Explanation:
The force acting on the sled is F = 6.20 N. Since it is acting at an angle of 35° to the horizontal, its horizontal component which moves the sled forward is Fcos35. This force is the net force on the sled. So,
Fcos35 = ma where m = mass of sled = 4.60 kg and a = acceleration of sled
a = Fcos35/m = 6.20cos35/4.60 = 1.1 m/s².
We now know its acceleration. To find the sleds speed after time t = 1.15 s, we use v = u + at where u = initial velocity of sled = 0 m/s (since it starts from rest)
Substituting the remaining values of a and t into the equation, we have
v = u + at = 0 + 1.1 × 1.15 = 1.27 m/s
So, the sled goes 1.27 m/s fast after 1.15 s
If the sled starts at rest, it is going with a speed of 1.27m/s after being pulled for 1.15secs
In order to get the velocity of the sled after being pulled, we will use the equation of motion
v = u + at
u is the initial velocity
a is the acceleration of the sled
t is the time taken
First, we need to get the acceleration of the sled using Newton's second law;
[tex]\sum F_x = ma_x\\Fcos35^0=4.60a_x\\6.20cos35^0=4.60a_x\\5.0787 = 4.60a_x\\a_x=\frac{5.0787}{4.60}\\a_x= 1.10m/s^2[/tex]
Substitute the acceleration into the equation of motion above:
[tex]v = u + at\\v =0+1.1(1.15)\\v=1.27m/s[/tex]
Hence if the sled starts at rest, it is going with a speed of 1.27m/s after being pulled for 1.15secs
Learn more here: https://brainly.com/question/13029733